The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.2478/macvetrev-2022-0031
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Criteria of Ketoprofen and its Cyclooxygenase-2 Inhibition in Mice: Influence of Xylazine Administration

Abstract: The objective of this study was to examine the effect of ketoprofen with or without combination with xylazine on the level of cyclooxygenase-2 in mice. The intraperitoneal (i.p.) dose of ketoprofen and xylazine that caused an analgesic response in half of the mouse population was 1.26 mg/kg and 6.63 mg/kg, respectively. Serum cyclooxygenase-2 concentration (activity) in the control mice was 16.94 ng/ml. The ketoprofen-treated group (2.52 mg/kg, i.p.) decreased the cyclooxygenase-2 concentration by 58% (7.16 ng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Xylazine administration increased the C 0.083 h (from 60.14 to 69.82 µg/mL) and AUC 0-∞ (from 1925.48 to 2361.32 h*µg/mL) of carprofen in castrated goat kids. Xylazine raised the AUC 0-∞ and peak concentration values of meloxicam in castrated goats and ketoprofen in mice, which was similar to our findings [7,42]. In this study, xylazine was administered 10 min before carprofen.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Xylazine administration increased the C 0.083 h (from 60.14 to 69.82 µg/mL) and AUC 0-∞ (from 1925.48 to 2361.32 h*µg/mL) of carprofen in castrated goat kids. Xylazine raised the AUC 0-∞ and peak concentration values of meloxicam in castrated goats and ketoprofen in mice, which was similar to our findings [7,42]. In this study, xylazine was administered 10 min before carprofen.…”
Section: Discussionsupporting
confidence: 88%
“…Xylazine administration reduced the Cl T of carprofen from 2.08 to 1.69 mL/h/kg in castrated male goats. Xylazine also reduced the Cl T of meloxicam in castrated goats and ketoprofen in mice [7,42]. E body of carprofen after alone and co-administered with xylazine in castrated goat kids was 0.0087 and 0.0081, respectively.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…At the level of visceral pain, nimesulide and aspirin decreased the contractions of the abdomen (writhing reflex) which were induced by acetic acid. The ED100 of nimesulide was superior to that of aspirin in reduction of the number of writhing reflexes in the percentage of nimesulide (66%) in comparison to aspirin (46%) which following the previous study proved that nimesulide outperformed the diclofenac (nonselective COX2 inhibitors) in analgesic effect at assayed writhing test in mice [28][29][30][31]. Other previous studies confirmed that NSAIDs had various anti-hyperalgesic actions than nimesulide which appears to be specially more efficient and rapid acting against inflammatory nociceptive in comparison to diclofenac, celecoxib, and rofecoxib [13] which was proven in the present study that nimesulide (preferential COX2 inhibitor) having more analgesic effect than aspirin (non-selective COX inhibitor).…”
Section: Discussionmentioning
confidence: 66%